Does marketing widen borders? Cross-country price dispersion in the European car market - Eyal Dvir; Georg Strasser (European Central Bank (ECB), 2017)
We study cross-country price differences in the European market for new passenger cars based on detailed pricing and technical data. Car prices in Europe converged until the year 2003, but not thereafter. Within the EU 15 countries the price range of the median model in 2004 was close to 20 percent. We document a source of international price differentiation, which is not related to distribution and border costs, but instead systematically linked to product features. Price dispersion increases with the market segment and varies significantly across models. Marketing appears to position identical goods differently in each country, for example by feature bundles tailored to local consumer preferences. Both the convergence before the actual reduction of barriers to arbitrage and the systematic international price differentiation by product feature point to active pricing-to-market strategies that treat countries as marketing regions.
Keywords: F15; F31; L11; L62; D22; 330; arbitrage; European car market; international price dispersion; law of one price; market segmentation